Implementasi Pelatihan Triase pada Basic Trauma Cardiac Life Support (BTCLS) sebagai Upaya Peningkatan Kesiapsiagaan Perawat dalam Kegawatdaruratan - Solehudin Solehudin; Arif Hidahatullah; Inas Syabanasyah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
The Basic Trauma Cardiac Life Support (BTCLS) training, which includes triage principles, is a strategic effort to enhance nurses’ preparedness in facing emergency situations. This article discusses the implementation of triage training in BTCLS as a means of developing nurses’ competencies in rapid assessment and priority decision-making for patient management using the START and ATS methods. Through a combination of theory, simulation, and practice, this training improves psychomotor skills, communication, and interprofessional coordination among healthcare providers in critical situations. As a result, nurses become more confident, responsive, and effective in delivering emergency care, which contributes to improved patient safety and the overall quality of healthcare services. This article emphasizes the importance of structured training as a foundation for strengthening triage systems and emergency management in healthcare facilities.